THE ANALYSIS OF THE EFFECT OF BRAND IMAGE, SERVICE PERFORMANCE, PORTFOLIO SERVICES, AND PHYSICAL EVIDENCES TOWARDS CUSTOMERS SATISFACTION OF “BTN BATARA” SAVINGS ACCOUNT AT PT BANK TABUNGAN NEGARA (PERSERO) Tbk, SEMARANG BRANCH OFFICE - Nailur Rofi’ah; Moch. Abdul Kodir; Moch. Muslikh (KEUNIS, 2020)
The objectives of this Final Report are to analyze and to obtain empirical evidences on the effect of brand image, service performance, portfolio services, and physical evidences towards customers satisfaction of “BTN Batara” Savings Account at PT Bank Tabungan Negara (Persero) Tbk, Semarang Branch Office. The population of this Final Report is all of the customers at PT Bank Tabungan Negara (Persero) Tbk, Semarang Branch Office. The sampling technique uses the Random Sampling Method amounting to 100 customers. The data used in this Final Report is the primary data obtained throough the distribution of questionnaires. The data analysis model uses the Multiple Linear Regression Analysis Model. Meanwhile, data analysis techniques use F Test, Coefficient of Determination (R2), and t Test.The Results of the analysis and discussion show that the variables of brand image, service performance, portfolio services, and physical evidences simultaneously have a significant effect towards customers satisfaction at PT Bank Tabungan Negara (Persero) Tbk, Semarang Branch Office. Partially, variable of brand image and physical evidences each have positive and significant effects towards customers satisfaction at PT Bank Tabungan Negara (Persero) Tbk, Semarang Branch Office. Meanwhile, variable of service performance does not have positive effect nor it is not significant. While portfolio services have positive effect but it is not significant towards customers satisfaction at PT Bank Tabungan Negara (Persero) Tbk, Semarang Branch Office.